Interventions for increasing solid organ donor registration - Li, Alvin H (Cochrane Database Syst Rev, 2021)
BACKGROUND: A solution for increasing the number of available organs for transplantation is to encourage more individuals to register a commitment for deceased organ donation. However, the percentage of the population registered for organ donation remains low in many countries. OBJECTIVES: To evaluate the benefits and harms of various interventions used to increase deceased organ donor registration. SEARCH METHODS: We searched the Cochrane Kidney and Transplant Register of Studies up to 11 August 2020 through contact with an Information Specialist using search terms relevant to this review. Studies in the Register are identified through searches of CENTRAL, MEDLINE, and EMBASE, conference proceedings, the International Clinical Trials Register Search Portal and ClinicalTrials.gov. SELECTION CRITERIA: We included all randomised controlled trials (RCTs), cluster RCTs and quasi‐RCTs of interventions to promote deceased organ donor registration. We included studies if they measured self‐reported or verified donor registration, intention to donate, intention to register a decision or number of individuals signing donor cards as outcomes. DATA COLLECTION AND ANALYSIS: Two authors independently assessed retrieved studies and extracted data from included studies. We assessed studies for risk of bias. We obtained summary estimates of effect using a random‐effects model and expressed results as risk ratios (RR) (95% confidence intervals; CI) for dichotomous outcomes and mean difference (MD; 95% CI) or standardised mean difference (SMD; 95% CI) for continuous outcomes. In multi‐arm trials, data were pooled to create single pair‐wise comparisons. Analyses were stratified by specific intervention setting where available. MAIN RESULTS: Our search strategy identified 46 studies (47 primary articles, including one abstract) comprising 24 parallel RCTs, 19 cluster RCTs and 3 quasi‐RCTs. Sample sizes ranged from 138 to 1,085,292 (median = 514). A total of 16 studies measured registration behaviour, 27 measured intention to register/donate and three studies measured both registration behaviour and intention to register. Interventions were delivered in a variety of different settings: schools (14 studies), driver’s motor vehicle (DMV) centres (5), mail‐outs (4), primary care centres (3), workplaces (1), community settings (7) and general public (12). Interventions were highly varied in terms of their content and included strategies such as educational sessions and videos, leveraging peer leaders, staff training, message framing, and priming. Most studies were rated as having high or unclear risk of bias for random sequence generation and allocation concealment and low risk for the remainder of the domains. Data from 34/46 studies (74%) were available for meta‐analysis. Low certainty evidence showed organ donation registration interventions had a small overall effect on improving registration behaviour (16 studies, 1,294,065 participants: RR 1.30, 95% CI 1.19 to 1.43, I(2) = 84%), intention to register/donate (dichotomous) (10 studies, 10,838 participants: RR 1.21, 95% CI 1.03 to 1.42, I(2) = 91%) and intention to register/donate (continuous) (9 studies, 3572 participants: SMD 0.23, 95% CI 0.11 to 0.36, I(2) = 67%). Classroom‐based interventions delivered in a lecture format by individuals from the transplant community may be effective at increasing intention to register/donate (3 studies, 675 participants: RR 1.33, 95% CI 1.15 to 1.55, I² = 0%). Community interventions targeting specific ethnic groups were generally effective at increasing registration rates (k = 5, n = 4186; RR 2.14, 95% CI 1.35 to 3.40, I² = 85%), although heterogeneity was high. In particular, interventions delivered in the community by trained peer‐leaders appear to be effective (3 studies, 3819 participant: RR 2.09, 95% CI 1.08 to 4.06, I² = 87%), although again, the data lacked robustness. There was some evidence that framing messages (e.g. anticipated regret) and priming individuals (e.g. reciprocity) in a certain way may increase intention to register/donate, however, few studies measured this effect on actual registration. Overall, the studies varied significantly in terms of design, setting, content and delivery. Selection bias was evident and a quarter of the studies could not be included in the meta‐analysis due to incomplete outcome data reporting. No adverse events were reported. AUTHORS' CONCLUSIONS: In our review, we identified a variety of approaches used to increase organ donor registration including school‐based educational sessions and videos, leveraging peer leaders in the community, DMV staff training, targeted messaging and priming. The variability in outcome measures used and incompleteness in reporting meant that most data could not be combined for analysis. When data were combined, overall effect sizes were small in favour of intervention groups over controls, however, there was significant variability in the data. There was some evidence that leveraging peer‐leaders in the community to deliver organ donation education may improve registration rates and classroom‐based education from credible individuals (i.e. members of the transplant community) may improve intention to register/donate, however, there is no clear evidence favouring any particular approach. There was mixed evidence for simple, low‐intensity interventions utilising message framing and priming. However, it is likely that interest in these strategies will persist due to their reach and scalability. Further research is therefore required to adequately address the question of the most effective interventions for increasing deceased organ donor registration.